Translating knowledge management visions into strategies - Ceruti, Monique; Williams, Angel; Bedford, Denise (Emerald Publishing Limited, 2019)
There is a critical point of failure for every knowledge management effort: when the strategy is isolated from the organization, and when there is no vision anchoring the strategy. This book guides professionals in learning to create a foundation for 21st century knowledge organizations.
Includes index.
Keywords: Knowledge management.; Business & Economics -- Management.; elektronické knihy; electronic books